A P. falciparum NF54 Reporter Line Expressing mCherry-Luciferase in Gametocytes, Sporozoites, and Liver-Stages - Marin-Mogollon, Catherin; Salman, Ahmed M.; Koolen, Karin M. J.; Bolscher, Judith M.; van Pul, Fiona J. A.; Miyazaki, Shinya; Imai, Takashi; Othman, Ahmad Syibli; Ramesar, Jai; van Gemert, Geert-Jan; Kroeze, Hans; Chevalley-Maurel, Severine; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Transgenic malaria parasites expressing fluorescent and bioluminescent proteins are valuable tools to interrogate malaria-parasite biology and to evaluate drugs and vaccines. Using CRISPR/Cas9 methodology a transgenic Plasmodium falciparum (Pf) NF54 line was generated that expresses a fusion of mCherry and luciferase genes under the control of the Pf etramp10.3 gene promoter (line mCherry-luc@etramp10.3). Pf etramp10.3 is related to rodent Plasmodium uis4 and the uis4 promoter has been used to drive high transgene expression in rodent parasite sporozoites and liver-stages. We examined transgene expression throughout the complete life cycle and compared this expression to transgenic lines expressing mCherry-luciferase and GFP-luciferase under control of the constitutive gapdh and eef1a promoters. The mCherry-luc@etramp10.3 parasites express mCherry in gametocytes, sporozoites, and liver-stages. While no mCherry signal was detected in asexual blood-stage parasites above background levels, luciferase expression was detected in asexual blood-stages, as well as in gametocytes, sporozoites and liver-stages, with the highest levels of reporter expression detected in stage III-V gametocytes and in sporozoites. The expression of mCherry and luciferase in gametocytes and sporozoites makes this transgenic parasite line suitable to use in in vitro assays that examine the effect of transmission blocking inhibitors and to analyse gametocyte and sporozoite biology.